Rheological and Velocity Profile Measurements of Blood in Microflow Using Micro-particle Image Velocimetry - Pitts, Katie Lynn (Université d'Ottawa / University of Ottawa, 2013)
Microhemodynamics is the study of blood flow in small vessels, usually on the order of 50 to 100 µm. The in vitro study of blood flow in small channels is analogous to the in vivo study of the microcirculation. At this scale the Reynolds and Womersly numbers are significantly less than 1 and the viscous stress and pressure gradient are the main determinant of flow. Blood is a non-homogeneous, non-Newtonian fluid and this complex composition and behavior has a greater impact at the microscale. A key parameter is the shear stress at the wall, which is involved in many processes such as platelet activation, gas exchange, embryogenesis and angiogenesis. In order to measure the shear rate in these blood flows the velocity profile must be measured. The measured profile can be characterized by the maximum velocity, the flow rate, the shear rate at the wall, or a shape parameter reflecting the bluntness of the velocity profile. The technique of micro-particle image velocimetry (µPIV) was investigated to measure the velocity profiles of blood microflows. The material of the channel, the type of tracer particles, the camera used, and the choice in data processing were all validated to improve the overall accuracy of µPIV as a blood microflow measurement method. The knowledge gained through these experiments is of immediate interest to applications such as the design of lab-on-a-chip components for blood analysis, analysis of blood flow behavior, understanding the shear stress on blood in the microcirculation and blood substitute analysis. Polymer channels were fabricated from polydimethylsiloxane (PDMS) by soft lithography in a clean room. PDMS was chosen for ease of fabrication and biocompatibility. The contacting properties of saline, water, and blood with various polymer channel materials was measured. As PDMS is naturally hydrophilic, surface treatment options were explored. Oxygenated plasma treatment was found to be less beneficial for blood than for water. The choice of camera and tracer particles were validated. Generally, for in vivo studies, red blood cells (RBCs) are used as tracer particles for the µPIV method, while for in vitro studies, artificial fluorescent micro particles are added to the blood. It is demonstrated here that the use of RBCs as tracer particles creates a large depth of correlation (DOC), which can approach the size of vessel itself and decreases the accuracy of the method. Next, the accuracy of each method is compared directly. Pulsed images used in conjunction with fluorescing tracer particles are shown to give results closest to theoretical approximations. The effect of the various post-processing methods currently available were compared for accuracy and computation time. It was shown that changing the amount of overlap in the post-processing parameters affects the results by nearly 10%. Using the greatest amount of correlation window overlap with elongated windows aligned with the flow was shown to give the best results when coupled with a image pre-processing method previously published for microflows of water. Finally the developed method was applied to a relevant biomedical engineering problem: the evaluation of blood substitutes and blood viscosity modifiers. Alginate is a frequently used viscosity modifier which has many uses in industry, including biomedical applications. Here the effect of alginate on the blood rheology, i.e., the shape of the velocity profile and the maximum velocity of blood flow in microchannels, was investigated. Alginate was found to blunt the shape of the velocity profile while also decreasing the shear rate at the wall. Overall, the accuracy of µPIV measurements of blood flows has been improved by this thesis. The work presented here has extended the known methods and accuracy issues of blood flow measurements in µPIV, improved the understanding of the blood velocity profile behavior, and applied that knowledge and methods to interesting, relevant problems in biomedical and biofluids engineering.
Keywords: hemorheology; biofluids; cross-correlation; flow visualization; red blood cells; microhemodynamics